Relationship between cigarette smoking and hearing loss in China: A cross-sectional study in Zhejiang province - Dahui Wang*; Yajun Zhu*; Chenhui Li; Yi Wang; Shichang Wang; Shuang Wu; Shiyan Zhang; Liangwen Xu (Tobacco Induced Diseases, 2021)
Introduction Hearing loss and cigarette smoking are major challenges that affect public health in China. Revealing the effect of smoking on hearing loss in the Chinese general population is critical for hearing health protection. We investigated the relationship between smoking status and hearing loss in China, especially in stratified sex and age groups.